Table of Content - - (Journal of engineering sciences and information technology, 2025)
Table of Content: 1. Challenges of implementing sustainable design and construction in building projects in kuwait Eng. Mohamed Ezzat Elnakhely, Eng. Faisal Sadeq Alhawaj 2. Leading Innovation Using AI in Higher Education Institutions: A Systematic Review to Analyze Strategies and Challenges Mr. Sami Munahi Almeqati 3. Transformation of Safety Management in Mega Projects: Exploring the Impact of Smart Technology and Digitization on Performance and Safety in Saudi Arabia Dr. Mohammad Abdullah Barnawy ,Dr. Samiyah Rafan Althaqafy ,Mr. Faris Omar Batawi 4. Improvement of Cooperative Spectrum Sensing in Rayleigh Fading and AWGN Environments for Cognitive Radio Networks Eng. Rayan Abdelazeem Haboub, Prof. Khalid Hamid Bilal 5. Sustainable Community participation in heritage conservation plans: A systematic literature review comparing international frameworks with practices Eng. Ghada Fathy Abdel-Fattah, Prof. Muhammad Ibrahem Gabr, Co-Prof. Mohamed Ezzeldin